(untitled) (The Pakistan Development Review, 2004)
Globalisation and financial sector reforms in developing economies have ushered in a sea change in the financial architecture of the economies. In the contemporary scenario, the activities in the financial markets and their relationships with the real sector have assumed significant importance. Correspondingly, researches are also being conducted to understand the current working of the economic and the financial system in the new scenario. Interesting results are emerging particularly for the developing countries where the markets are experiencing new relationships which are not perceived earlier. The analysis on stock markets has come to the fore since this is the most sensitive segment of the economy. The stock markets of emerging economies have been of vital importance to the global investment community. Since emerging markets are more volatile than the well developed stock market, therefore the emerging markets tend to be unrelated to one another and with the developed markets. Numerous investors worldwide select to diversify their funds across the emerging markets.